Taraxasterol inhibits TGF-β1-induced epithelial-to-mesenchymal transition in papillary thyroid cancer cells through regulating the Wnt/β-catenin signaling. (December 2021) - Zhu, J; Li, X; Zhang, S; Liu, J; Yao, X; Zhao, Q; Kou, B; Han, P; Wang, X; Bai, Y; Zheng, Z; Xu, C
Taraxasterol (TAR) is a kind of active compound extracted from dandelion and its molecular structure resembles steroid hormones. Recently, TAR has been reported to show an anti-tumor activity. However, the specific role of TAR in papillary thyroid cancer (PTC) has not been clarified. In this study, we investigated the effect of TAR on PTC cell migration, invasion and epithelial-to-mesenchymal transition (EMT) induced by TGF-β1. PTC cells were exposed to TGF-β1 (5 ng/mL) and then treated with different concentrations of TAR. We found that TAR showed no obvious cytotoxicity below 10 μg/mL but notably reduced migration and invasion of TGF-β1-treated PTC cells. Moreover, TAR treatment decreased MMP-2 and MMP-9 levels, and obviously affected the expression of EMT markers. We also observed that Wnt3a and β-catenin levels were significantly increased in TGF-β1-treated PTC cells while TAR inhibited these effects in a concentration-dependent manner. Additionally, activation of the Wnt pathway by LiCl attenuated the suppressive effect of TAR on TGF-β1-induced migration, invasion and EMT in PTC cells. Taken together, we highlighted that TAR could significantly suppress TGF-β1-regulated migration and invasion by reversing the EMT process via the Wnt/β-catenin pathway, suggesting that TAR may be a potential anti-cancer agent for PTC treatment.